Integrin Subunit Alpha M, ITGAM Nonsynonymous SNP Is Associated with Knee Osteoarthritis among Thais: A Case-Control Study - Kamphon Intharanut; Plaiwan Suttanon; Oytip Nathalang (Current Issues in Molecular Biology, 2023)
Knee osteoarthritis (OA), which is one of the most common degenerative joint diseases, presents a multifactorial etiology, involving multiple causative factors including genetic and environmental determinants. Four human neutrophil antigen (HNA) systems can be determined using each HNA allele by single-nucleotide polymorphisms (SNPs). However, there are no data on HNA polymorphisms and knee OA in Thailand, so we investigated the association of HNA SNPs and knee OA in the Thai population. In a case-control study, detection of HNA-1, -3, -4, and -5 alleles by polymerase chain reaction with sequence-specific priming (PCR-SSP) was performed in participants with and without symptomatic knee OA. Logistic regression models were used to estimate the odds ratio (OR) and 95% confidence interval (CI) between cases and controls. Among 200 participants, 117 (58.5%) had knee OA; 83 (41.5%) did not and were included as controls in this study. An integrin subunit alpha M (ITGAM) nonsynonymous SNP, rs1143679, was markedly associated with symptomatic knee OA. The ITGAM*01*01 genotype was identified as an important increased risk factor for knee OA (adjusted OR = 5.645, 95% CI = 1.799–17.711, p = 0.003). These findings may contribute to our understanding of the application prospects for therapeutic approaches to knee OA.